Complete laparoscopic pancreaticoduodenectomy: our experience of the first case - Joshi, Mukund Raj; Regmee, Sujan; Bohara, Tanka Prasad; Chakradhar, Rupesh; Shrestha, Mandesh (Journal of Society of Surgeons of Nepal, 2019)
Laparoscopic pancreaticoduodenectomy was described in 1994. It is considered the most challenging abdominal surgery. Although the procedure was found to be feasible in initial reports, the benefits were not considered favorable. In recent days, with the increasing experience of surgeons, acceptable outcomes are being observed and have been found to be technically beneficial and oncologically safe in selective cases in experienced hands. We performed the procedure in a 42-year-old gentleman with good operative and post-operative outcomes. The patient’s follow-up for six post-operative months seems satisfactory. The operation took 840 minutes with minimal blood loss. The resected specimen was adequate and satisfactory from an oncological and technical point of view. The patient developed some inherent complications of the procedure in the post-operative period. He recovered well. Details of the case and technical aspects are being discussed.